Career transitions and identity: a discursive psychological approach to exploring athlete identity in retirement and the transition back into elite sport - Cosh, S.; LeCouteur, A.; Crabb, S.; Kettler, L. (Qualitative Research in Sport, Exercise and Health, 2013)
Athletes` career transitions have received widespread research attention and have been identified as potentially distressing for athletes. Yet, the transition back into elite sport following retirement, although rare, has not been a focus of research attention. The concept of athlete identity has been widely researched within sport psychology to give insight into the varied experiences of athletes, especially in relation to the transition out of elite sport. Accordingly, identity may provide additional insight into the transition back into competing at an elite level. Through adopting a discursive psychological approach to the examination of 84 newsprint media representations involving athletes and career transitions, the present study aims to explore dominant social understandings around athlete identity and the choices athletes make to compete (or not) in sport. In doing so, the aim is to add to existing literature around athlete identity and gain insight into the social contexts in which athletes choose to transition back into elite sport, as well as to extend the existing discursive psychological literature of sport and exercise into areas of athlete identity, career transition and the media. Returning to compete in elite sport was routinely depicted in media accounts as something that is not chosen, but as driven by emotion, compulsion and a need to play. Such representations of athletes construct their identity as necessarily motivated by emotion and compulsion.